2016
DOI: 10.1016/j.molp.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Association–Dissociation of Glycolate Oxidase with Catalase in Rice: A Potential Switch to Modulate Intracellular H 2 O 2 Levels

Abstract: Rapid and dynamic change in hydrogen peroxide (H2O2) levels can serve as an important signal to regulate various biological processes in plants. The change is realized by tilting the balance between its production and scavenging rates, in which membrane-associated NADPH oxidases are known to play a crucial role. Functioning independently from NADPH oxidases, glycolate oxidase (GLO) was recently demonstrated as an alternative source for H2O2 production during both gene-for-gene and non-host resistance in plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 118 publications
2
94
0
Order By: Relevance
“…GO activity, the most important enzymes involved in the production of H 2 O 2 in peroxisomes (Corpas, 2015) suffered strong down-regulation in APX1/2 plants, evidencing a strong synchrony between CAT and GO (Zhang et al, 2016). Recently we have reported that CAT inhibition by 3-AT in rice leaves induce reduction in GO activity, especially in peroxisomal APX4 knockdown mutants and these changes were related to lower H 2 O 2 accumulation (Sousa et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…GO activity, the most important enzymes involved in the production of H 2 O 2 in peroxisomes (Corpas, 2015) suffered strong down-regulation in APX1/2 plants, evidencing a strong synchrony between CAT and GO (Zhang et al, 2016). Recently we have reported that CAT inhibition by 3-AT in rice leaves induce reduction in GO activity, especially in peroxisomal APX4 knockdown mutants and these changes were related to lower H 2 O 2 accumulation (Sousa et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…CATs are also targets of excess copper toxicity, which leads to retarded seed germination in rice (Ye et al, 2014). A very recent study suggested that the physical association-dissociation of GLO (Glycolate Oxidase; H 2 O 2 producer) and CAT serve as a specific machinery to modulate H 2 O 2 levels in rice (Zhang et al, 2016). Moreover, a potential PEX5-CATA-SOD interaction relationship was suggested by our PPI analysis ( Figure 4C ).…”
Section: Discussionmentioning
confidence: 99%
“…The oxalate produced is then completely oxidized into CO 2 and H 2 O 2 by OsOXO3, an isoform of oxalate oxidase in rice that has a stable optimum pH ranging from 6.0 to 8.0 (Li et al, 2015). H 2 O 2 produced by the three reactions is scavenged by OsCATC, an isoform of catalase in rice leaves (Zhang et al, 2016). We named this bypass the GOC bypass after the three enzymes (glycolate oxidase, oxalate oxidase, catalase) used.…”
Section: Establishment Of a New Photorespiratory Bypass In Rice Chlormentioning
confidence: 99%